Source tracking using microbial community fingerprints: Method comparison with hydrodynamic modelling. (1st February 2017) - McCarthy, D.T.; Jovanovic, D.; Lintern, A.; Teakle, I.; Barnes, M.; Deletic, A.; Coleman, R.; Rooney, G.; Prosser, T.; Coutts, S.; Hipsey, M.R.; Bruce, L.C.; et al.
Abstract: Urban estuaries around the world are experiencing contamination from diffuse and point sources, which increases risks to public health. To mitigate and manage risks posed by elevated levels of contamination in urban waterways, it is critical to identify the primary water sources of contamination within catchments. Source tracking using microbial community fingerprints is one tool that can be used to identify sources. However, results derived from this approach have not yet been evaluated using independent datasets. As such, the key objectives of this investigation were: (1) to identify the major sources of water responsible for bacterial loadings within an urban estuary using microbial source tracking (MST) using microbial communities; and (2) to evaluate this method using a 3-dimensional hydrodynamic model. The Yarra River estuary, which flows through the city of Melbourne in South-East Australia was the focus of this study. We found that the water sources contributing to the bacterial community in the Yarra River estuary varied temporally depending on the estuary's hydrodynamic conditions. The water source apportionment determined using microbial community MST correlated to those determined using a 3-dimensional hydrodynamic model of the transport and mixing of a tracer in the estuary. While there were some discrepancies between the two methods, this investigation demonstrated that MST using bacterial community fingerprints can identify the primary water sources of microorganisms in an estuarine environment. As such, with further optimization and improvements, microbial community MST has the potential to become a powerful tool that could be practically applied in the mitigation of contaminated aquatic systems. Graphical abstract: Highlights: A novel source tracking method using microbial community fingerprints is proposed. Sources of water contamination to an estuary were estimated using SourceTracker. This new method was independently checked against a 3D hydrodynamic model.